Psychometric evidence of the Satisfaction with Life Scale (SWLS) in adult population of Metropolitan Lima, 2020 - Chiroque Crespo, Jackeline Gianella (2021)
The present study was conducted with the aim of analyzing evidence psychometric of the Scale of Satisfaction with Life (SWLS) in adult population of Metropolitan Lima, 2020. We evaluated 314 people, including 166 women and 148 men with an age range between 18 to 59 years. In addition, we applied the type of non-probability sampling by convenience, where people participated voluntarily. On the other hand, we employed the following instruments PANSI, SHS, UCLA to correlate them with the satisfaction. Among the results, evidence of validity was found in relation to other variables; in addition, a total variance of 70% of the instrument was obtained, the adjustment indices (TLI= .997, CFI= .998, RMSEA= .021 and SRMR= .021) indicated the one-dimensional SWLS; consequently, (α= .79 y ω= .80) coefficients demonstrate the reliability of the SWLS scale. In conclusion, the instrument has adequate psychometric evidence for use in the adult population of Metropolitan Lima.